Treatment differentiation between group music therapy and recreational choir singing for people with dementia and depression living in residential care homes: structured video analysis of the interventions in the MIDDEL trial - Bloska, Jodie; Ablewhite, Joanne; Rasing, Naomi; Janus, Sarah; Uçaner, Burçin; Gürkan, Barış; Gold, Christian; Vink, Annemieke; Schneider, Justine (Frontiers in Psychiatry, 2026)
IntroductionMusic-based interventions are often implemented in residential dementia care to support quality of life and wellbeing, and to minimize neuropsychiatric symptoms such as depression. A recent international randomized controlled trial called MIDDEL (“Music Interventions for Dementia and Depression in Elderly Care”) compared efficacy of two popular music-based interventions: recreational choir singing (RCS) and group music therapy (GMT). The current study was undertaken to determine similarities and differences between the delivery of these two interventions within the MIDDEL trial.MethodsTo determine treatment differentiation between RCS and GMT in MIDDEL, we undertook structured video analysis of a random sample of the available session videos from the trial. For each intervention, the videos were analyzed against a predefined checklist, which included items across three music-based activities: singing familiar songs, instrument playing and movement to music. Pearson’s chi-square tests were used to assess whether the type of intervention significantly influenced the delivery of the checklist items.ResultsA sample of 65 session videos (GMT: 32; RCS: 33) were analyzed from MIDDEL sessions delivered in the Netherlands, Türkiye and the UK. Overall, the interventions differed significantly in their implementation, x2(1) = 101.39, p = <.001, with a small effect size (Cramer’s V = 0.257). Singing familiar songs was used in all GMT and RCS sessions, although there were some specific differences in terms of how facilitators engaged the participants within musical interactions. GMT sessions regularly incorporated playing instruments, whereas this was rare within RCS sessions. There was no difference in the use of movement to music, which occurred in around a third of sessions in both GMT and RCS.DiscussionThe current findings confirm treatment differentiation between the two music-based interventions delivered as part of the MIDDEL trial. The results may indicate distinctive characteristics of professional music therapy as compared to community choir singing within residential dementia care, while also identifying overlaps in practice. Understanding the differences and similarities between these two popular music-based interventions can guide future research and inform their use in clinical practice.